Two new dwarfgobies (Teleostei: Gobiidae) from the Ryukyu Islands, Japan: Eviota flavipinnata and Eviota rubrimaculata - Suzuki, Toshiyuki; Greenfield, David W.; Motomura, Hiroyuki (Zootaxa, 2015)
Two new species of Eviota from Yoron Island, the Ryukyu Islands, Japan, are described. Both species belong to the cephalic sensory-canal pore system pattern 2 (lacking only the H [IT] pore); have some pectoral-fin rays branched; have a dorsal/anal-fin formula of 9/8; no dark spot over the ural centrum; no prominent distinct dark spots on the pectoral-fin base; no postocular spots; and no strong dark spots on the caudal fin. The species share the most characters with E. afelei, E. bimaculata and E. punctulata, but differ from Eviota afelei and E. punctulata by having two versus three dark marks over the anal-fin base, and from Eviota bimaculata by lacking the two dark, prominent occipital spots present in that species. Both species differ from all other described species of Eviota in fresh coloration. Eviota flavipinnata has bright golden-yellow dorsal fins and an orange anal fin, and a fifth pelvic-fin ray that is 12% the length of the fourth ray. Eviota rubrimaculata has clear dorsal fins with red spots, large red spots on the body, and lacks the fifth pelvic-fin ray.